26.3: Invited Paper: Development of Advanced Materials for Printed OLED Displays. (28th November 2018) - Ren, Xiaofan; Zou, Yunlong; Fennimore, Adam; Hlaing, Htay; Skulason, Hjalti
Abstract : Solution processing of OLED is desirable because it allows for large area OLED displays with low manufacturing cost. Historically the device performance achievable with solution processing lagged that of evaporation. DuPont has focused on developing OLED materials for soluble technologies, as well as working with our partners on our proprietary printing process. Our performance data shows that with our latest generation materials and process steps, ink‐jet printed device performance suitable for TV application can now be achieved.